Morality and moral theory : a reappraisal and reaffirmation - Louden, Robert B., 1953- (Oxford University Press, 1992)
Contemporary philosophers are increasingly sceptical toward both morality and moral theory. Some argue that moral theory is a radically misguided enterprise which does not illuminate moral practice, while others simply deny the value of morality in human life. The author responds to the arguments of both 'anti-morality' and 'anti-theory' sceptics.